Disruption of Hydrogen Bonding Network Decreases Catalytic Diversity of Chloroperoxidase via Abolishing Both Chlorination and Dismutation Activities - Elena Shersher; Armando D. Pardillo; Xiaotang Wang (Journal of Enzymes, 2024)
The perpendicular orientation of the proximal alpha helix to the heme plane in chloroperoxidase (CPO) maximizes the influence of its intrinsic helix dipole that has been shown to reduce the “push-effect”, thereby increasing the heme redox potential and fine-tuning the catalytic capabilities of CPO. We investigated the effects of a disruption of the hydrogen bonding network between R26-N37 and A27-N33, formed by the proximal alpha helix, on the CPO structural stability and catalytic profile using site-directed mutagenesis and spectroscopy. The mutant CPO (R26A, N33A, and R26A/N33A) exhibited significant tertiary structural changes and distinct heme coordination, likely, due to destabilization of the proximal helix as a result of the disruption of the proximal hydrogen bonding network. In line with these observations, biochemical characterizations showed that all mutants displayed dramatically different activity profiles relative to that of the WT CPO. Mutant epoxidation and peroxidation activities were markedly enhanced, especially in the R26A/N33A CPO mutant. Moreover, all mutant CPO enzymes exhibited broader pH profiles in both epoxidation and peroxidation activities, including a shift in the optimal peroxidation activity towards pH 3.5 as opposed to pH 2.75. Conversely, the dismutation activity (pH 3.0-5.5) was almost completely lost while chlorination activity (pH 2.75-5.0) was virtually non-existent in all CPO mutants. Our results demonstrate the important role the R26-N37 and A27-N33 hydrogen bond pairs play in the heme coordination and tertiary structure of CPO defining its catalytic capabilities, and also suggest the importance of the proximal helix stability and orientation.
Keywords: chloroperoxidase